What is unique about running a school? Consequences for the formation of directors - Antúnez Marcos, Serafín (Avances en Supervisión Educativa, 2011)
The training of principals of schools is a prerequisite for improving education. The training process will be more relevant and effective if designed and implemented mainly considering the peculiarities that distinguish the practice of management in an educational institution from which it takes place in other organizations. Considering three of those idiosyncrasies are some tips for selecting appropriate training content which should be given priority. It also notes that training can be done through various methods and devices, including advice and support from the Educational Inspectorate can occupy a prominent place.